Antigenic and genotypic characterization of rabies virus isolates from bats from Botucatu city and region - Menozzi, B. D.; Carrieri, M. L.; Oliveira, R. N.; Pereira, V. B. R.; Langoni, H. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Texto em inglês